Odpowiedzi

2009-11-05T21:41:39+01:00
A) -3x=2x-10
-5x=-10
x=2
b) 2x-2=7-x
3x=9
x=3
c) 10=4-2x
2x=-6
x=-3
d) -(2x-1)=4
-2x+1=4
-2x=3
x=-1,5
e) 2(x+1)=x
2x+2=x
x=-2
f) 2t-(3t+1)=6
2t-3t-1=6
-t=7
t=-7
g) -(4+x)=2(3-x)
-4-x=6-2x
x=10
h) 3(y+6)-y=2(y+9)
i) (x-7)-2(3x+5)=3
2009-11-05T21:42:51+01:00
A) -3x=2x-10
-3x-2x=-10
-5x=-10 /:(-5)
x=2

b) 2x-2=7-x
2x+x=7+2
3x=9 /:3
x=3

c) 10=4-2x
-2x=10-4
-2x=6 /:(-2)
x=-3

d) -(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3 /:(-2)
x=-3/2

e) 2(x+1)=x
2x+2=x
2x-x=-2
x=-2

f) 2t-(3t+1)=6
2t-3t-1=6
2t-3t=6+1
-t=7 /*(-1)
t=-7

g) -(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10

h) 3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0

i) (x-7)-2(3x+5)=3
x-7-6x-10=3
x-6x=3+7+10
-5x=20 /:(-5)
x=-4
2009-11-05T21:47:32+01:00
A. -3x=2x-10
-5x=-10 /:(-5)
x=2
b. 2x-2=7-x
3x=9 /:3
x=3
c. 10=4-2x
2x=-6 /:(2)
x=-3
d. -(2x-1)=4
-2x+1=4
-2x=3 /:(-2)
x=-3/2
e. 2(x+1)=x
2x+2=x
x=-2
f. 2t-(3t+1)=6
2t-3t-1=6
-t=7 /*(-1)
t=-7
g. -(4+x)=2(3-x)
-4-x=6-2x
x=10
h. 3(y+6)-y=2(y+9)
3y+18-y=2y+18
0=0
i. (x-7)-2(3x+5)=3
x-7-6x-10=3
-5x=20 /:(-5)
x=-4